Developmental models of the carrion beetle Thanatophilus rugosus (Linnaeus, 1758) (Coleoptera: Silphidae) - S. Montoya-Molina (Nature Portfolio, 2021)
Abstract Coleoptera are currently considered a fundamental tool to help solve criminal investigations, allowing forensic entomologists to estimate post-mortem intervals and obtain other ecology-related information. Thanatophilus rugosus (Linnaeus, 1758) is an important necrophagous beetle distributed through most of the Palaearctic region, where it is readily found on human bodies and animal carcasses. In this study, the new thermal summation models for all the developmental stages of Thanatophilus rugosus are provided. Beetles were reared at six different constant and ecologically relevant temperatures (12, 14, 16, 18, 20, and 22 °C), and their developmental times were measured. Thermal summation constants were calculated for each developmental stage (egg, three larval instars, post-feeding stage, and pupa).